Performance determinants and leg kinematics in the BMX supercross start - Gross, M. A. D.; Schellenberg, F.; Lüthi, G.; Baker, M.; Lorenzetti, S. (Journal of Science and Cycling, 2017)
In competitive BMX racing, a fast start, that is, the shortest possible elapsed time and the highest possible instantaneous velocity at the end of the starting phase, is crucial for obtaining a favourable position in the middle portion of the race and the best possible final ranking. This study aimed first to evaluate several influencing factors for their relative importance in determining starting performance in competitive BMX racers. Also, this study describes basic leg kinematics during the first few pedal strokes of the starting phase. Subjects performed practice starts on a supercross ramp while various kinematic and kinetic parameters were obtained using a modified powermeter crank and a 3-d motion capture system. Data were analyzed with linear regression with starting performance as the output. The results show that an early turnaround during the preparation maneuver (countermovement) prior to the gat drop and a powerful first pedal stroke, with both a high torque and equivalent cadence, have the most influence on overall starting performance. End velocity is also related to attained peak cadence and the torque at peak cadence. Regarding leg kinematics, extension velocities are similar to ballistic jumps with relatively high loads. Thus, BMX racers should focus technical training on a quick and early turnaround in the preparation maneuver and strength training should be focused on developing strength and power at relatively high loads.